Three-year outcomes after Aquablation therapy compared to TURP: results from a blinded randomized trial - Gilling, Peter; Barber, Neil; Bidair, Mohamed; Anderson, Paul; Sutton, Mark; Aho, Tev; Kramolowsky, Eugene; Thomas, Andrew; Cowan, Barrett; Kaufman, Jr, Ronald P; Trainer, Andrew; Arther, Andrew; et al. (Canadian journal of urology, 2020)
To compare 3-year efficacy and safety after prostate resection with Aquablation therapy or transurethral resection of the prostate (TURP) for the treatment of lower urinary tract symptoms related to benign prostate hyperplasia (BPH). One hundred and eighty-one patients assigned to either Aquablation therapy or TURP were followed for 3 years postoperatively. Patients and follow up assessors were blinded to treatment. Assessments included International Prostate Symptom Score (IPSS), Male Sexual Health Questionnaire (MSHQ-EjD), International Index of Erectile Function (IIEF) and uroflow. Over 3 years of treatment, improvements in IPSS scores were statistically similar across groups. Mean 3-year improvements were 14.4 and 13.9 points in the Aquablation and TURP groups, respectively (difference of 0.6 points, 95% CI -3.3-2.2, p = .6848). Similarly, 3-year improvements in Qmax were 11.6 and 8.2 cc/sec (difference of 3.3 [95% CI -0.5-7.1] cc/sec, p = .0848). At 3 years, PSA was reduced significantly in both groups by 0.9 and 1.1 ng/mL, respectively; the reduction was similar across groups (p = .5983). There were no surgical retreatments for BPH beyond 20 months for either Aquablation or TURP. Three-year BPH symptom reduction and urinary flow rate improvement were similar after TURP and Aquablation therapy. No subjects required surgical retreatment beyond 20 months postoperatively. (ClinicalTrials.gov number, NCT02505919).